Milton Melo charitable education and neurofunctional association: An approach to care for students with Autism Spectrum Disorder (ASD) - Rodrigues , Rosiomar Lobato Pinheiro; Ribeiro , Mílvio da Silva (Seven Editora, 2024)
Due to the complexity and diversity of symptoms presented by people with Autism Spectrum Disorder (ASD), it is essential to have specialized institutions committed to the development and well-being of these individuals. The municipality of Abaetetuba, located in the Amazon region of Brazil, stands out for its rich biodiversity of fauna and flora. ABENMM is a non-profit entity founded by 20 families, with the support of neurologist Madacilina Melo Teixeira and professor Abdinaldo Rodrigues Ferreira. Maintained through an agreement with the municipal government, the association operates in the philanthropic, cultural, welfare, educational and rehabilitation areas. This article aims to present an analysis of the services offered, through direct observation and analysis of the results obtained, through an interview with an employee, it seeks to understand how this institution contributes to the development of its students with disabilities, among these, those with Autism Spectrum Disorder-ASD. DOI:https://doi.org/10.56238/sevened2024.018-005